PENGEMBANGAN E-LKPD BERBASIS PROBLEM BASED LEARNING UNTUK MELATIH KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS V SDN SELOPURO 1 NGAWI - Devita Sabrina; Candra Dewi; Nur Samsiyah (STKIP Subang, 2023)
There’s problem with the development of students' mathematical understanding, so it is necessary to develop alternative interactive teaching materials. This study aims to develop Student Worksheets (LKPD) as a means to learn mathematical concepts and hone students' problem-solving skills. In this study, the R&D (Research and Development) approach was used with the ADDIE model which consisted of five stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques used included observation, interviews, documentation and questionnaires aimed at media and material experts as well as teachers and fifth grade students at SDN Selopuro 1 Ngawi. The validation process applies a Likert scale which consists of four answer choices. Data analysis is done by applying certain formulas and drawing conclusions. The compiled E-LKPD draft contains several components, namely the cover containing student identity and author biographies, preface and table of contents, instructions for using LKPD, KI and KD, GPA and learning objectives as well as learning materials that contain interactive mathematics material. The results of e-worksheet validation by the material and media expert validator obtained a score of